Биомеханическое исследование прочности восстановленных связок латерального отдела голеностопного сустава - Красноперов, С. Н.; Головаха, М. Л.; Краснопьоров, Сергій Миколайович; Головаха, Максим Леонідович; Krasnoperov, S. N.; Golovakha, M. L. (Ин-т патологии позвоночника и суставов им. проф. М. И. Ситенко НАМН Украины, 2014)
В последнее время в специальной литературе появляется все больше сообщений об использовании артроскопических методик реконструкции повреждений ПМТС и МПС, однако данных о прочности их восстановления при помощи шва либо якорных фиксаторов под артроскопическим контролем нет. Целью нашего биомеханического эксперимента было определить прочность восстановленных связок латерального отдела голеностопного сустава при помощи методик, применяющихся при операциях под артроскопическим контролем (П-образный шов, якорные фиксаторы). Arthroscopic techniques of reconstruction in cases of the anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) are widely known. However, biomechanical research of strength of restored ligaments under arthroscopic control using suture or anchor devices was not conducted. Objective: to find out the strength of restoration of lateral ligaments of the ankle joint with help of techniques under arthroscopic control (П-shaped suture, anchor devices). Materials: sixteen cadaver ankle joints were used. It was revealed that damage of the ATFL leads to significant increasing in anterior displacement of talus relative to the tibia and to slight increasing of its varus deviation. In case of damage of the CFL, conversely, varus deviation of talus increases significantly and its anterior dislocation increases insignificantly. The strength of the restored ATFL with using of the П-shaped suture was 85 N, and with help of the anchor device was 88.8 N, corresponding to 59 and 62 % of the strength of the intact ligament. The strength of the restored CFL using П-shaped suture was 83.8 N, and with help of the anchor device was 86.3 N, i.e. 24 and 25 % of the strength of the intact ligament. Strength characteristics revealed correspond to these ones in cases of reconstruction of the ligaments with using of the Brostrom technique. Therefore, we believe that early loading (except inversion) in special orthopedic shoes will not affect the outcomes of treatment. Артроскопічні методики реконструкції ушкод- жень передньої малогомілково-надп’яткової (ПМНЗ) та малогомілково-п’яткової (МПЗ) зв’язок широко відомі. Проте біомеханічних досліджень міцнос- ті відновлених зв’язок під артроскопічним конт- ролем за допомогою шва або якірних фіксаторів не проводилось. Мета: з’ясувати міцність відновлення зв’язок латерального відділу надп’ятково-гомілкового суглоба за допомогою методик, які застосовують в операціях під артроскопічним контролем (П-подібний шов, якірні фіксатори). Матеріалом дослідження були 16 надп’ятково-гомілкових суглобів трупів. Встановлено, що ушкод- ження ПМНЗ призводить до значного збільшення переднього зміщення надп’яткової кістки відносно великогомілкової та незначного збільшення її варусного відхилення. У разі ушкодження МПЗ, навпаки, значно підвищується варусне відхилення надп’яткової кістки й незначно її переднє зміщення. Міцність відновленої ПМНЗ за допомогою П-подібного шва становила 85 Н, а якірного фіксатора — 88,8 Н, що відповідає 59 і 62 % міцності неушкодженої зв’язки. Міцність відновленої МПЗ за допомогою П-подібного шва становила 83,8 Н, а якірного фіксатора — 86,3 Н, тобто 24 і 25 % міцності неушкодженої зв’язки. Отримані міцнісні характеристики відповідають таким у разі реконструкції зв’язок з використанням методики Brostrom. Тому вважаємо, що раннє навантаження (за винятком інверсійного) в спеціальному ортопедичному взутті не вплине на результати лікування.
Biomechanical study of the strength of the reconstructed lateral ligaments of the ankle joint
Keywords: голеностопный сустав; повреждение связок; хирургическое лечение; ankle joint; damage of the ligaments; surgical treatment; надп’ятково-гомілковий суглоб; ушкодження зв’язок; хірургічне лікуванння